Mechanical and Microstructural Properties of AA 1030 Aluminum Alloy Plates Joined by Friction Stir Welding - Ozdemir, N.; Sarsilmaz, F.; Buyukarslan, S. (Carl Hanser Verlag, 2010)
In this study, the mechanical and microstructural properties of friction stir welded AA 1030 aluminum alloys were investigated experimentally. The friction stir welding trials were conducted under different rotational speed, traverse speed and stirrer geometry conditions. The welding zones were investigated under optical microscopy. Tensile tests and microhardness studies were also employed to the study. On the other hand, the fracture characterizations of samples were examined by scanning electron microscopy (SEM). Four distinct zones were revealed through the joints as discussed below. It was experimentally found that the most important welding parameter on mechanical properties was traverse speed. The rotational speed was the second ranking factor while the stirrer geometry seemed to have less influence on mechanical properties.
Mechanische und mikrostrukturelle Eigenschaften von durch Rührreibschweißen gefügten AA 1030-Aluminiumplatten
Keywords: Parameters; Zone; Tool